2023
DOI: 10.1002/ecm.1560
|View full text |Cite
|
Sign up to set email alerts
|

Partner fidelity and environmental filtering preserve stage‐specific turtle ant gut symbioses for over 40 million years

Abstract: Sustaining beneficial gut symbioses presents a major challenge for animals, including holometabolous insects. Social insects may meet such challenges through partner fidelity, aided by behavioral symbiont transfer and transgenerational inheritance through colony founders. We address such potential through colony‐wide explorations across 13 eusocial, holometabolous insect species in the ant genus Cephalotes. Through amplicon sequencing, we show that previously characterized worker microbiomes are conserved in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 188 publications
4
37
0
Order By: Relevance
“…As with their free‐living counterparts (Little et al, 2008), the stability of symbiont communities is affected by ecological and evolutionary processes. These include microbial competition and cooperation (Consuegra, Grenier, Akherraz, et al, 2020; Figueiredo & Kramer, 2020; Johnston & Rolff, 2015), priority effects and environmental filtering (Bongrand & Ruby, 2019; Dal Grande et al, 2018; David et al, 2016; Devevey et al, 2015; Hu et al, 2022; Lee et al, 2013; Sprockett et al, 2018; Youngblut et al, 2019), and selection acting at the host level on symbiont‐conferred phenotypes (e.g. Andongma et al, 2022; Hughes et al, 2014; Itoh et al, 2019; Rossi et al, 2015; Theis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As with their free‐living counterparts (Little et al, 2008), the stability of symbiont communities is affected by ecological and evolutionary processes. These include microbial competition and cooperation (Consuegra, Grenier, Akherraz, et al, 2020; Figueiredo & Kramer, 2020; Johnston & Rolff, 2015), priority effects and environmental filtering (Bongrand & Ruby, 2019; Dal Grande et al, 2018; David et al, 2016; Devevey et al, 2015; Hu et al, 2022; Lee et al, 2013; Sprockett et al, 2018; Youngblut et al, 2019), and selection acting at the host level on symbiont‐conferred phenotypes (e.g. Andongma et al, 2022; Hughes et al, 2014; Itoh et al, 2019; Rossi et al, 2015; Theis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In other social Hymenoptera, larval microbiota also differ from those of adults and can play important roles. For example, in Cephalotes turtle ants, microbiota change substantially as the larvae develop (Hu et al, 2023), exhibiting a consistent successional pattern of unknown functional importance. Likewise, honeybee larval microbiota are very different from those of adult bees and can play important roles (Anderson et al, 2018; Kapheim et al, 2015; Martinson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent 16S rRNA gene-amplicon studies of microbiota of sponges and coral-reef invertebrates found significant signals of host-species specificity consistent with codiversification in multiple bacterial and archaeal families, including the Endozoicomonadaceaea, Spirochaetaceaea, and Nitrosopumilaceae (O'Brien et al, 2021;Pollock et al, 2018). Similarly, 16S rRNA gene-amplicon studies have detected evidence of co-diversification between gut bacteria and ant lineages (Hu et al, 2023).…”
Section: Signals Of Co-diversification In Complex Microbiotamentioning
confidence: 97%